A Bibliometric Analysis of Studies Concerning Policy Issues in Covid-19 Pandemic - Nguyen, The Thang; Dinh-Hai Luong; Hong-Lien Nguyen; Thi-Phuong Thao Vu; Hoai-Thu Nguyen (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2022)
This research analysed the studies of policy on issues related to COVID-19. The results show the most productive countries, the most frequently cited sources, the most co-occurred topics of studies concerning policy issues since the epidemic was a breakout at the beginning. The data in this research were collected from the Scopus database with two search terms,